Workshop Guru SDN Melayu 7 Banjarmasin dalam Menyusun Soal Cerita Berbasis Kearifan Lokal untuk Meningkatkan Kemampuan Berpikir Kreatif - Aminah Ekawati; Winda Agustina; Hajjah Rafiah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
SDN Melayu 7 is located in Banjarmasin Tengah and has implemented the 2013 curriculum. There are some problems found from interviews with the principal and some teachers, namely students, are more faced with routine questions and are required to be able to solve problems in the story of the question. While the teacher has difficulty making story questions that are easily understood by students. This activity aims to prepare teachers to know how to arrange story problems based on local wisdom in South Kalimantan to improve creative thinking skills. The approach used is active participant learning. The activity is divided into two stages, and stage I is focused on the question of story problems based on local wisdom in South Kalimantan, while in stage II, it is focused on the question of story problems based on local wisdom that can improve the ability to think creatively. To measure the success of each stage, an understanding questionnaire was given, and the work of the participant groups were seen. The activity is said to be successful if the average questionnaire comprehension is at least 75%. The results of the activity showed the level of understanding of the participants reached 93.61% in stage I and 91.94% in stage II. Also seen from the results of group work it can be concluded that participants can understand well the explanations given by the speakers.